The biochemical kinetics underlying actin movement generated by one and many skeletal muscle myosin molecules. - Baker, Josh E (2002)
To better understand how skeletal muscle myosin molecules move actin filaments, we determine the motion-generating biochemistry of a single myosin molecule and study how it scales with the motion-generating biochemistry of an ensemble of myosin molecules. First, by measuring the effects of various ligands (ATP, ADP, and P(i)) on event lifetimes, tau(on), in a laser trap, we determine the biochemical kinetics underlying the stepwise movement of an actin filament generated by a single myosin molecule. Next, by measuring the effects of these same ligands on actin velocities, V, in an in vitro motility assay, we determine the biochemistry underlying the continuous movement of an actin filament generated by an ensemble of myosin molecules. The observed effects of P(i) on single molecule mechanochemistry indicate that motion generation by a single myosin molecule is closely associated with actin-induced P(i) dissociation. We obtain additional evidence for this relationship by measuring changes in single molecule mechanochemistry caused by a smooth muscle HMM mutation that results in a reduced P(i)-release rate. In contrast, we observe that motion generation by an ensemble of myosin molecules is limited by ATP-induced actin dissociation (i.e., V varies as 1/tau(on)) at low [ATP], but deviates from this relationship at high [ATP]. The single-molecule data uniquely provide a direct measure of the fundamental mechanochemistry of the actomyosin ATPase reaction under a minimal load and serve as a clear basis for a model of ensemble motility in which actin-attached myosin molecules impose a load.